If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x=-11/13
We move all terms to the left:
x-(-11/13)=0
We get rid of parentheses
x+11/13=0
We multiply all the terms by the denominator
x*13+11=0
Wy multiply elements
13x+11=0
We move all terms containing x to the left, all other terms to the right
13x=-11
x=-11/13
x=-11/13
| 11z-5=z+7 | | 9–s=2 | | 14-2x3+16=L | | -3(4-n)-5=7 | | (n-5)/6+(n+3))/7=11/21 | | 3x+(2x+5)=(2x+10)+(2x-15)=360 | | n/400=3 | | m+7m+3=19 | | 3.7x-7.61=8.3 | | x+11/2=-8 | | -1=t | | 2(x-2)=-4+32 | | 420x+69=1738 | | 9x-29=12x+31 | | 1-r-3r=-15 | | m/100=17 | | (8x−2)+(8x−2)=3x+2 | | 7=−5(n−4)−37=−5(n−4)−3 | | 18−(−f)=91 | | 11x-56=24+6x | | 5x+7-3x3=-9 | | 5x-27÷3=4 | | 9q2+48q+64=0 | | (3x+2)+(3x+2)=8x−2 | | |-1+n|=8 | | X-10=-3x+6 | | -6x+12=2(6-8x) | | √x+5=3 | | 2x+0,4x=2943 | | 7/3+3m/7=64/21 | | k/2+1-1K=2k | | 11x-12+3x+18=x |